Re-purposing is needed for beneficial bugs, not for the drugs - Ram, Hari; Dastager, Syed G. (International Microbiology, 2019)
Between 150 and 200 species of plants, insects, birds or mammals go extinct every day. We do not have any idea what the global extinction rate for microorganisms is. What is clear is that we have already lost a maximum number of the microbes that used to live in and on our skins. Many of our microbial partners are facing extinction as we apply selection pressures that are unprecedented in our long-standing relationships. Recent estimates are that we have lost at least one third of the diversity of our skin microbiome. Every day, most of us bath or shower in water that contains chlorine or fluorine; these additives do a great job of killing pathogenic microbes, but they are probably not helping our skin microbiome. Most of the people apply cosmetic products every day, as these products contain preservatives that prevent microbial growth on the shelf. These same chemicals may well kill microbes on the skin. The daily use of high-pH soaps probably will not help microbial life that is adapted to living on the skin's natural pH of 5. The rise in the rate of C-section births from around 5% in 1970 to more than 30% today is likely to be a contributing factor. Vaginal microbes seed our skins at birth and C-sections disrupt this process. The overuse of broad-spectrum antibiotics has contributed to the loss of our microbial partners in all body sites and the skin is no exception. It is now clear that skin is an ecosystem that is dependent on commensal microbes for optimal health. In general, a diverse ecosystem is a healthy ecosystem that is robust in the face of change. Low-diversity ecosystems are more fragile and susceptible to dysbiosis. Eczema and acne rates have increased rapidly over the last 50 years. These diseases are almost unknown in hunter-gatherer communities. Now, we face two exciting challenges: finding out which species matter and how to get them back.
Keywords: Drugs; Dysbiosis; Microbiome; Probiotics